2019
DOI: 10.1016/j.phro.2019.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric impact of placement errors in optically stimulated luminescent in vivo dosimetry in radiotherapy

Abstract: Introduction: Studies have suggested that optically stimulated luminescent dosimeters (OSLDs) can be used for in vivo dosimetry of intensity-modulated radiation therapy (IMRT) and volumetric-modulated arc therapy (VMAT). Clinical uncertainties such as placement error have not been thoroughly investigated. The purpose of this work was to measure OSLD placement error in a clinical sample and analyze its dosimetric impact. Methods and materials: The analysis consisted of three parts: first, quantification of plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…By combining entrance with exit measurements, differences in patient anatomy between planning and delivery can also be detected [24] . However, the transition from simple conformal fields to intensity-modulated techniques such as intensity-modulated radiation therapy (IMRT) and volumetric modulated arc therapy (VMAT) has limited the usefulness of point measurements [25] , [26] , particularly when bearing in mind the additional uncertainty due to placement error, which can substantially impact measured-to-planned dose agreement of point detectors in high gradient regions, demonstrating the criticality of accurate dosimeter placement for IMRT and VMAT treatments [27] .…”
Section: Current Ivd Methodsmentioning
confidence: 99%
“…By combining entrance with exit measurements, differences in patient anatomy between planning and delivery can also be detected [24] . However, the transition from simple conformal fields to intensity-modulated techniques such as intensity-modulated radiation therapy (IMRT) and volumetric modulated arc therapy (VMAT) has limited the usefulness of point measurements [25] , [26] , particularly when bearing in mind the additional uncertainty due to placement error, which can substantially impact measured-to-planned dose agreement of point detectors in high gradient regions, demonstrating the criticality of accurate dosimeter placement for IMRT and VMAT treatments [27] .…”
Section: Current Ivd Methodsmentioning
confidence: 99%
“…However, as the clinical reports show, patient entrance doses obtained for the IVD of complex RT techniques vary significantly due to the chip’s placement errors. As a result, the dosimetric uncertainty can be even doubled [ 4 ]. Therefore, one of the solutions to avoid dose discrepancies is to migrate from point-based in vivo dosimetry to planar or volumetric methods, enabling spatial dose measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Accurate measurement of small radiation fields is a well-known challenge, due to loss in charged particle equilibrium. The potential of Al 2 O 3 :C point detectors for small field dosimetry was successfully accessed by many authors [30] , [31] . Several works demonstrated that plastic scintillators measured higher output factors than an ionization chamber, silicon diode and/or radiographic film [32] , due to difficulties to correct for the Cherenkov radiation and the differences in the active volumes of the detectors.…”
Section: Discussionmentioning
confidence: 99%
“…When we integrated a sequence of 10 images (resulting in a 200 ms integrated image), the signal-to-noise ratio improved and the difference observed in the valleys were 2–3%, with FHWM = 5.5 ± 0.2 mm. It is possible that part of the overresponse observed in the valley region were due to the films material’s specific energy dependency for energies below 100 keV [30] , [36] .…”
Section: Discussionmentioning
confidence: 99%